2016
DOI: 10.1177/2050640615581577
|View full text |Cite
|
Sign up to set email alerts
|

A common genetic variant of fucosyltransferase 2 correlates with serum carcinoembryonic antigen levels and affects cancer screening in patients with primary sclerosing cholangitis

Abstract: Background: Primary sclerosing cholangitis (PSC) patients are at increased risk of biliary tract cancer, and carcinoembryonic antigen (CEA) serum levels might be used for screening. Objective: To examine cancer screening with CEA in PSC patients and analyse how serum CEA levels are affected by genetic variants of fucosyltransferase (FUT) 2 and 3. Methods: In a retrospective cohort analysis we evaluated CEA levels in 226 PSC patients, including 19 with biliary malignancy, and investigated how FUT2 and FUT3 SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…11 It was subsequently identified as a risk factor for dominant stenosis (DS) and cholangitis 12 and further studies revealed that FUT2 in combination with FUT3 significantly affects cancer screening in PSC patients. 13,14 Based upon these recent findings that the CA19-9 level in PSC patients with and without biliary malignancy depends on the FUT2 and FUT3 genotype, we hypothesized that these genotypes will also influence CA19-9 levels in PSC patients with cholestasis and SBC. We therefore designed this trial to investigate the influence of cholestasis, SBC and the FUT2/3-genotype on maximum CA19-9 levels in PSC patients.…”
Section: Introductionmentioning
confidence: 99%
“…11 It was subsequently identified as a risk factor for dominant stenosis (DS) and cholangitis 12 and further studies revealed that FUT2 in combination with FUT3 significantly affects cancer screening in PSC patients. 13,14 Based upon these recent findings that the CA19-9 level in PSC patients with and without biliary malignancy depends on the FUT2 and FUT3 genotype, we hypothesized that these genotypes will also influence CA19-9 levels in PSC patients with cholestasis and SBC. We therefore designed this trial to investigate the influence of cholestasis, SBC and the FUT2/3-genotype on maximum CA19-9 levels in PSC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of patients exhibit single nucleotide polymorphisms within the fucosyltransferase ( FUT ) 3 gene that cause a loss of CA19‐9 synthesis . However, these patients might benefit from screening with carcinoembryonic antigen, which also is not influenced by bacterial cholangitis . Whereas the use of CA19‐9 biosynthesis groups, based on single nucleotide polymorphisms of FUT2 and FUT3, leads to diagnostic improvement, in our experience, CA19‐9 values show high interpersonal variability.…”
Section: Introductionmentioning
confidence: 82%
“…The study was previously approved by the ethics committee of the University Hospital Heidelberg. The database, which had already been used as a basis for previously published studies, contained all available CA19‐9 and carcinoembryonic antigen values for each included patient until diagnosis of BTC, liver transplantation (LT), death, or until 31 December 2014, whichever came first. CA19‐9 and carcinoembryonic antigen values were derived by chart review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinoembryonic antigen (CEA) is a glycoprotein involved in cellular adhesion, and a tumor marker that is frequently elevated in gastrointestinal malignancies. A retrospective cohort analysis demonstrated fucosyltransferase 2 and 3 genotyping can also enhance sensitivity of CEA measurements, especially in those patients whom do not express CA 19‐9 …”
Section: Increased Risk For Cancers Incidence and Surveillancementioning
confidence: 99%